Pengaruh Harga Kualitas Produk Dan Strategi Promosi Terhadap Minat Membeli Uapik Abu Snack Jakarta - Rani; Ayu Azizah; Syahrir; Khoirul Ulum (Journal of Trends Economics and Accounting Research, 2023)
This research analyzes and examines the influence of product quality, price, and promotion strategy on the intention to buy steamed abu snacks in Jakarta. This research was conducted at Uapik Abu Snack in Jakarta which is located on Jalan Syaridin, South Jakarta, and was carried out using quantitative research. This type of research data with quantitative descriptive. The nature of the research uses explanatory descriptive. The population of this research is customers who buy at Uapik Abu Snack, totaling 130 respondents with a sample of 100 respondents. the sampling technique used is probability sampling. Data analysis using multiple linear regression analysis, F test, T-test, coefficient of determination test, classic assumption test used as normality test, multicollinearity test, and heteroscedasticity test. The results of the partial test of the variable price on buying interest is -0,334 are significant 0.000 <0.05, testing the product quality variable on buying interest is 0.589 with a significance of 0.000 <0.05, and the promotion strategy variable on buying interest is 0.723 with a significant 0.000 <0.05 it can be concluded that product quality, price, and promotion strategy have a positive and significant effect on the intention to buy Uapik Abu Snack in Jakarta, then H1, H2, H3 are accepted.